2021
DOI: 10.1186/s41181-021-00144-x
|View full text |Cite
|
Sign up to set email alerts
|

18F-labeled tracers targeting fibroblast activation protein

Abstract: Background Cancer-associated fibroblasts are found in the stroma of epithelial tumors. They are characterized by overexpression of the fibroblast activation protein (FAP), a serine protease which was already proven as attractive target for chelator-based theranostics. Unfortunately, the value of gallium-68 labeled tracers is limited by their batch size and the short nuclide half-life. To overcome this drawback, radiolabeling with aluminum fluoride complexes and 6-fluoronicotinamide derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…Others have attempted to label multiple FAPIs with [ 18 F] AlF and found that 18 F-FAPI-74 gave the most favorable results in an in vitro study, and they performed a visualization study in a patient with metastatic non–small cell lung cancer and obtained conclusions similar to those of Giesel et al. ( 20 , 39 ).…”
Section: Targeting Cafs For Imagingmentioning
confidence: 73%
“…Others have attempted to label multiple FAPIs with [ 18 F] AlF and found that 18 F-FAPI-74 gave the most favorable results in an in vitro study, and they performed a visualization study in a patient with metastatic non–small cell lung cancer and obtained conclusions similar to those of Giesel et al. ( 20 , 39 ).…”
Section: Targeting Cafs For Imagingmentioning
confidence: 73%
“…Given the intrinsic advantages of 18 F‐labeled compounds, investigators have begun labeling FAPI‐based radiotracers with radiofluorine, including the use of 18 F‐aluminium fluoride in place of 68 Ga in the chelator moieties of existing compounds 96 . A subset of such radiotracers has been found to have favorable pharmacokinetics with high tumor‐to‐background ratios 97 …”
Section: Examples Of Molecular Imaging Utilizationmentioning
confidence: 99%
“…Specifically, we detail techniques in optical and near‐infrared (NIR) imaging, magnetic resonance imaging (MRI), and nuclear medicine techniques, including single‐photon emission computed tomography (SPECT) and positron emission tomography (PET) (Table 1). 4‐119 We also provide specific examples from translational science and cancer clinical care of the utilization of molecular imaging, with a particular focus on the use of these methods to guide and improve patient management. Finally, we delineate the challenges faced by the field and the potential benefits of overcoming them.…”
Section: Introductionmentioning
confidence: 99%
“…While [ 18 F]AlF-FAPI-42, the NOTA-derivative of FAPI-04, showed hepatobiliary excretion, Lindner et al succeeded with FAPI-74, the analog precursor lacking the difluoro substitution at the pyrrolidine ring. For the corresponding radiotracers [ 18 F]AlF-FAPI-74 and 68 Ga-FAPI-74, Giesel et al demonstrated an equal performance compared to 68 Ga-FAPI-04 PET/CT in clinical applications [ 22 , 23 ]. Independently, Jiang et al reported preclinical results and a first-in-man study of [ 18 F]AlF-labeled NOTA-FAPI-04 (FAPI-42) [ 24 ].…”
Section: Fap Targeting Compoundsmentioning
confidence: 99%
“…With the anticipation of these uncertainties, the development of the FAPI-tracers focused more on tumor retention and pharmacokinetics than the absolute uptake or IC 50 values. Another aim was to exclude hepatobiliary excretion and, especially, to reduce the exposure of non-target tissues, such as bone marrow or salivary glands [ 17 , 18 , 23 , 25 ].…”
Section: Fap Targeting Compoundsmentioning
confidence: 99%